Kontribusi Etika Politik Islam Terhadap Penyelesaian Korupsi di Indonesia - Andika Dwi Putra; Zahir, Rifyan; Razak, Syaiful Akbar; Kurniati (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The social and political challenges faced by Muslim countries, such as conflict and corruption, necessitate a comprehensive approach rooted in strong values. Prolonged conflict and rampant corruption have impeded development and eroded public trust in the government. This research seeks to investigate the role of Islamic political ethics in resolving conflicts and curbing corruption in modern Muslim countries. The research methodology employed is qualitative analysis, utilizing a literature review to assess the principles of Islamic political ethics, including justice, transparency, and accountability, as well as their application within contemporary political contexts. The research findings demonstrate that Islamic political ethics offer a robust moral framework for cultivating a more equitable and responsive government. The principle of justice encompasses the fair allocation of resources and the safeguarding of individuals' and vulnerable groups' rights. Transparency and accountability in decision-making processes can mitigate corruption and enhance public trust. While challenges persist, such as varying interpretations and the instrumentalization of religion for political purposes, with the requisite commitment, Islamic political ethics can bolster social and political progress in present-day Muslim countries. In conclusion, Islamic political ethics hold considerable promise in surmounting social and political challenges by upholding the values of justice, transparency, and accountability. It is anticipated that the recommendations derived from this research will contribute to the enhancement of governance in Muslim countries.